2011
DOI: 10.2527/jas.2010-3095
|View full text |Cite
|
Sign up to set email alerts
|

Heifer development systems: Dry-lot feeding compared with grazing dormant winter forage1

Abstract: Two hundred ninety-nine Angusbased, nulliparous heifers (253 ± 2 kg initial BW) from 3 production years were utilized to compare traditional postweaning dry lot (DL) development with a more extensive winter grazing system utilizing a combination of corn residue and winter range (EXT). Heifers developed in the DL were offered a common diet after the weaning period for 208 d in yr 1, 194 d in yr 2, and 150 d in yr 3 until breeding. Heifers developed in EXT grazed corn residue for 135 d in yr 1, 106 d in yr 2, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 25 publications
6
31
3
2
Order By: Relevance
“…Research reports published through the 1980s demonstrated a much greater negative effect of limited postweaning growth on age of puberty and subsequent pregnancy rate (Short and Bellows, 1971;Wiltbank et al, 1985;Patterson et al, 1989). More recent studies (Buskirk et al, 1995;Freetly and Cundiff, 1997;Lynch et al, 1997;Funston and Larson, 2011) suggest less of a negative impact of delayed puberty on pregnancy rates. Evidenced by the findings in the current study, decreased winter BW gain of MG heifers in the extensive BG system resulted in greater BW gain during the breeding season, which may explain overall pregnancy rates.…”
Section: Heifer Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Research reports published through the 1980s demonstrated a much greater negative effect of limited postweaning growth on age of puberty and subsequent pregnancy rate (Short and Bellows, 1971;Wiltbank et al, 1985;Patterson et al, 1989). More recent studies (Buskirk et al, 1995;Freetly and Cundiff, 1997;Lynch et al, 1997;Funston and Larson, 2011) suggest less of a negative impact of delayed puberty on pregnancy rates. Evidenced by the findings in the current study, decreased winter BW gain of MG heifers in the extensive BG system resulted in greater BW gain during the breeding season, which may explain overall pregnancy rates.…”
Section: Heifer Performancementioning
confidence: 99%
“…Developing heifers to attain a target BW of 55% of Roberts et al, 2007, Roberts et al, 2009Martin et al, 2008;Larson et al, 2011) that demonstrated that developing replacement heifers to lighter target BW ranging from 50 to 57% of mature BW before breeding reduced development costs, but had no negative effect on reproductive performance or subsequent calf performance. Funston and Larson (2011) reported that developing heifers on corn residue or winter range reduced development costs by $45/ pregnant heifer. The advantages of developing heifers in extensive winter grazing systems are decreased stored feed requirements, direct deposition of manure nutrients on the wintering site, and reduced yardage costs (Jungnitsch et al, 2011;Kelln et al, 2011).…”
Section: Economic Analysismentioning
confidence: 99%
“…Porém, de nada vale esta prenhez precoce das novilhas se as mesmas não repetirem cria, sendo perdida toda a alimentação diferenciada para acelerar o processo de puberdade e acasalamento (27) , bem como sendo descartados por infertilidade animais geneticamente superiores em rebanhos que trabalham com melhoramento genético (29) . Isso é determinado, provavelmente, pelo maior tempo de recuperação das vacas, com maiores pesos, condições corporais e, consequentemente, melhor resposta reprodutiva (9) .…”
Section: Resultsunclassified
“…The NRC (1996) recommends a target BW of 60% mature cow weight at the beginning of the breeding season to obtain high reproduction rates. However, studies carried out in the last decades comparing intensive with extensive systems found that lower target weights (50-57% of the mature weight) reduce production costs and do not negatively affect reproductive performance (Funston and Deutscher, 2004;Roberts et al, 2009;Funston and Larson, 2011;Mulliniks et al, 2013). Considering that the geographical region of the farm and the applied production system do not allow for heavy mature and weaning weights, heifers need to achieve a higher percentage of the mature weight of a cow to reach puberty.…”
Section: Discussionmentioning
confidence: 99%